Contrast-enhanced ultrasound of granular cell tumor in breast: A case report with review of the literature - Wang, Huanyu; Feng, Duo; Zou, Tianhui; Liu, Yao; Wu, Xiaoqin; Zou, Jiawei; Huang, Rong (Frontiers in Oncology, 2022)
Granular cell tumor (GCT) is a rare, predominantly benign tumor of Schwann cell origin. Granular cell tumor of the breast (GCTB) can mimic carcinoma on breast imaging. We herein present a rare case of GCTB who recurred in the contralateral breast, the contrast-enhanced ultrasonography (CEUS) findings of which we believe have never been described. The high similarity between the clinical and imaging manifestations of breast cancer makes its differential diagnosis difficult. In this report, we describe the CEUS findings of a less common type of GCTB, discuss the potential value of CEUS to differentiate benign breast lesions from malignant ones, and briefly review the literature.